2022-RA-672-ESGO Comparison of quality of life in patients with platinum-sensitive recurrent ovarian, fallopian tube and peritoneal cancer treated with trabectedin plus pegylated liposomal doxorubicin (PLD) or standard platinum-based therapy: Data look of the NOGGO S16/COMPASS trial. (20th October 2022) - Chekerov, Radoslav; Deryal, Mustafa; Aktas, Bahriye; Röhle, Robert; Stürzebecher, Annika; Battista, Marco J; Kurbacher, Christian M; Wimberger, Pauline; Lorenz, Ralf; Barinoff, Jana; Rogmans, Gunther; Kosse, Jens; et al.
Abstract : Introduction/Background: Despite recent progress regarding surgical and medical management of primary ovarian cancer, relapses are still frequent and one of the most critical challenges in the clinical routine. There is a broad consensus that quality of life (QoL) should be one of the most relevant goals of any therapy in relapsed ovarian cancer. Methodology: We report the results of a data look of the multicentre, randomized (1:1), active-controlled, open-label phase IV NOGGO-S16/COMPASS trial performed in patients with recurrent, platinum-sensitive, ovarian, peritoneal or fallopian tube cancer. The scope of this trial is to evaluate QoL with EORTC QLQ-C30 and QLQ-OV28 questionnaires during/after chemotherapy either with platinum/taxane-free combination of trabectedin (Yondelis ® ) plus PLD or with standard platinum-based chemotherapy comprising combination of carboplatin with PLD, gemcitabine or paclitaxel. The current data look serves to characterise the included patient population. Results: Data from 76 patients screened have been analysed. Patients have a median age of 63 years (range: 21–82), the performance status score of 0/1 was recorded in 75 patients (98.7%), and most are BRCA-negative (77.4%). They are diagnosed with primary ovarian carcinoma (83.6%), primary peritoneal carcinoma (9.6%) and fallopian carcinoma (6.8%), and 79% of patients have a grade 3 histopathological staging. Poly (ADP-ribose) polymerase inhibitors or bevacizumab were given as prior maintenance therapy to 15.3% and 76.4% of patients, respectively. Overall, 60% of patients had a platinum-free interval of >12 months before randomization and 45.8% of patients finished COMPASS trial as per protocol. The main reasons for withdrawal were progression under treatment (18.6%), toxicity (15.3%), death (13.6%) and patient wish (6.8%). Post-protocol maintenance therapy was given to 23.8% of patients. No differences in patient characteristics were observed. Conclusion: Based on this data look no significant signal for a non-inferiority of the study arms have been observed. Study is ongoing and open for recruitment.